Speech Acts Analysis on Hate Speech Commentary on Anies Rasyid Baswedan’s Twitter - Sondang Manik; Yarman Ndraha; Donna Ria Pasaribu (Jurnal Scientia, 2022)
This research discusses Speech acts analysis of hate speech based commentary on Anies Rasyid Baswedans’ Twitter. The purpose of this research is to find out the types of “Speech Acts” based on commentary on Anies Baswedans’ Twitter (AB) and the speech acts found in the category of the “Hate Speech” on ABs Twitter. The research was descriptive qualitative research. The research utilized Speech Acts theory of Searle (1996) in analyzing the data. The steps of this research included identification of data, categorization and analyzing the data. The answer to the first problem of research findings show that the types of illocutionary acts found on Anies Baswedan‟s twitter consist of assertives, directives, commissives, expressive and declarative Assertives have the highest frequency of occourance or 50%. It is followed by expressive, directives, declarative, and commissives which occur 28%, 15%, 5% and 2% respectively. The answer of second problem of research findings show that speech acts found in the category of Hate Speech on ABs Twitter consist of insulting, defamation, provoking or incite and prejudice. Insulting have the highest frequency of occourance 80%. It is followed by provoking or incite, defamation, prejudice which occur 11%, 7%, 2% respectively. The highest frequency is 80% and netizens insulted the performance of AB in flooding case and rehabilitation of Monas.